Evaluation of Tomato Cultivars for Central Tarai of Nepal - Shrestha, Surendra Lal; Sah, Raj Lal (Nepal Journal of Science and Technology, 2015)
Tomato (Lycopersicon esculentum L.) is an important winter vegetable crop in Central Tarai. As compared to India (25 t/ha), the productivity of this crop in this area is quite low (17 t/ha). One of the major contributing factors of low productivity of tomato is the lack of suitable high yielding varieties under rice based cropping system. Ten tomato cultivars, 3 released check cultivars (Pusa ruby and CL-1131 open pollinated and Srijana hybrid cultivar), 7 superior cultivars from Initial Evaluation Trial in the past were planted in November 2005, 2006, 2009 and 2010 at RARS Parwanipur in rice-based cropping system. The trial was laid out in a randomized complete block design with four replications. Seedlings were transplanted on beds at 60x60 cm spacing fertilized with 120:100:60 NPK + 15 t compost per hectare. Results showed that cv. HRDTOM-005XHRDTOM-010 (30.64 t/ha) followed by Makis (28.90 t/ha) and cv. Srijana (28.87 t/ha) gave higher yield among the tested cultivars. These cultivars had given 47.0%, 38.7%, and 38.5% more yield as compared to commercial hybrid variety Manisha (20.84t/ha) whereas Bari-4 and CL-1131 had superior performance among the tested open pollinated cultivars. On the basis of overall performance, cultivars, HRDTOM-005XHRDTOM-010, Makis and Srijana hybrid cultivars, and Bari-4 and CL- 1131from open pollinated cultivars were selected and recommended for cultivation in central Tarai. DOI: http://dx.doi.org/njst.v15i2.12105 Nepal Journal Of Science and Technology, Vol. 15, No. 2, 2014, 11-16